The microbial challenge : science disease and public health - Krasner, Robert I (Jones & Bartlett, 2010)
Key Features Cover such vital topics as endangered species, overfishing, and current legislation that protects marine environments Includes chapter summaries and objectives, with an emphasis on critical thinking, and boxes addressing special topics of student interest Provides readers with a comprehensive look at modern threats facing today's oceans. About the Book: The Microbial Challenge: Science, Disease & Public Health Whether we realize it or not, microbes play an ever-present role in our daily lives. Food borne infections, epidemics and pandemics are frequently headline news. The Microbial Challenge: Science, Disease and Public Health, Second Edition, presents a fascinating look at humanmicrobe interactions and examines the disease producers while discussing how, with knowledge based preparation, we can live in harmony with microbes. It also discusses the ways in which beneficial microbes are involved in the cycles of nature and in the food industry, and how they are used as research tools. Ideal for undergraduate nonscience majors and allied and public health students, this unique text is a hybrid of microbiology and public health and includes material on prions, helminths (worms), biological warfare and terrorism, antibiotic resistance, the global impact of microbial diseases, and immunization. The text helps students better understand the biology of the microbial world and the societal factors that are both the cause and consequences of microbial disease. Contents Part 1: The Challenge Identifying the Challenge The Microbial World The Beneficial Aspects of Microbes: The Other Side of the Coin Bacteria Viruses Bacterial Genetics Part 2: Microbial Disease Concepts of Microbial Disease Epidemiology and Cycle of Microbial Disease Bacterial Diseases: Foodbornes and Waterborne Bacterial Diseases Viral Diseases Protozoans And Helminths and the Diseases they Cause Part 3: Meeting the Challenge The Immune Response Control of Microbial Diseases Partnerships in the